JOHN POLKINGHORNE AND BERNARD LONERGAN ON THE SCIENTIFIC STATUS OF THEOLOGY. - Hogan, Edward M. (Zygon: Journal of Religion & Science, 2009)
On the basis of his acquaintance with theoretical elementary particle physics, and following the lead of Thomas Torrance, John Polkinghorne maintains that the data upon which a science is based, and the method by which it treats those data, must respect the idiosyncratic nature of the object with which the science is concerned. Polkinghorne calls this the “accommodation” (or “conformity”) of a discipline to its object. The question then arises: What should we expect religious experience and theological method to be like if they are accommodated to the idiosyncratic nature of God? Polkinghorne's methodological program is typical of postcritical positions in the theology-science dialogue in holding that the fiduciary element in theological method is simply a species of the fiduciary element that is a de facto part of all knowing—in other words, theological method does not differ in fundamental kind from the methods of the natural sciences. But this program may contain the seeds of an alienation of theological method from the transcendence of God similar to the double self-alienation of theology described by Michael Buckley in At the Origins of Modern Atheism. I contend that something like Bernard Lonergan's position on how the method of faith seeking understanding is related to the methods of the natural sciences is exactly the sort of thing that one should expect on the supposition of Polkinghorne's principle of accommodation, at least if the God who is the object of theological science is transcendent. The way in which the divine differs from all other objects ought to be disclosed or reflected in religious experience and theological method. Polkinghorne charts the course for an accommodated theology, but it seems to be Lonergan who is more intent on following it.